Exploring the Effect of a Nature-based Virtual Reality Environment on Stress in Adolescents - Björling, Elin A.; Sonney, Jennifer; Rodriguez, Sofia; Carr, Nora; Zade, Himanshu; Moon, Soo Hyun (Frontiers in Virtual Reality, 2022)
Adolescent mental health is a growing public health issue, with 30% of teens reporting increased stress and 20% of adolescents suffering from depression. Given the scarcity and lack of scalability of mental health services available, the use of self-administered, evidence-based technologies to support adolescent mental health is both timely and imperative. We conducted a mixed-methods pilot study with 31 adolescents ages 14-19 (m=17.97) to explore the self-administration of a nature-based virtual reality tool. Participant use of the VR environment ranged from 1-10 sessions (m=6.6) at home over a two-week period while reporting their daily stress and mood levels. All participants completed all of the study protocols, indicating our protocol was feasible and the VR environment engaging. Post-study interviews indicated that most participants found the VR tool to be relaxing and helpful with stress. The themes of Calm Down, Relaxation, and Escape emerged to articulate the participants' experiences using the VR environment. Additionally, participants provided rich data regarding their preferences and activity in the VR environment as well as its effect on their emotional states. Although the sample size was insufficient to determine the impact on depression, we found a significant reduction in momentary stress as a result of using the VR tool. These preliminary data inform our own virtual reality environment design, but also provide evidence of the potential for self-administered virtual reality as a promising tool to support adolescent mental health.